Inducible nitric oxide synthase inhibitor, aminoguanidine improved Ki67 as a marker of neurogenesis and learning and memory in juvenile hypothyroid rats. Issue 5 (20th June 2020) - Alikhani, Vajiheh; Beheshti, Farimah; Ghasemzadeh Rahbardar, Mahboobeh; Marefati, Narges; Mansouritorghabeh, Fatemeh; Hosseini, Mahmoud
Abstract: Introduction: In the present study, the effect of inducible nitric oxide (NO) synthase inhibitor, aminoguanidine (AG) on neurogenesis indicators, learning and memory, and oxidative stress status in juvenile hypothyroid (Hypo) rats was evaluated. Method: The studied groups were including: (a) Control, (b) Hypo, (c–e) Hypo‐AG 10, Hypo‐AG 20, and Hypo‐AG 30. Hypothyroidism was induced in the groups 2–5 by adding propylthiouracil in drinking water (0.05%). AG (10, 20, or 30 mg/kg) was daily injected intraperitoneally in the groups 3–5. The rats of the groups 1 and 2 were injected by saline instead of AG. After 6 weeks treatment, Morris water maze (MMW) and passive avoidance (PA) tests were done. Deep anesthesia was then induced and the brain tissue was excised for biochemical parameters measuring. Results: Ki67 as a maker of neurogenesis and thiol, superoxide dismutase (SOD), and catalase (CAT) as oxidative stress indicators were decreased in the brain of Hypo group, whereas malondialdehyde (MDA) and NO metabolites were enhanced. AG improved Ki67, thiol, CAT, and SOD while decreased MDA and NO metabolites. The escape latency in the MWM test increased in the Hypo group. The spending time in the target quadrant in the probe test of MWM and step‐through latency in the PA test in the Hypo group was lower than Control group. AG reversed all the negative behavioral effects of hypothyroidism. Conclusion: These results revealed that AG improved neurogenesis, learning and memory impairments, and oxidative imbalance in the brain juvenile Hypo rats.